2014
DOI: 10.1523/jneurosci.4552-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking of Spiral Ganglion Neuron Firing Dynamics by Membrane Potential and Neurotrophin-3

Abstract: Type I spiral ganglion neurons have a unique role relative to other sensory afferents because, as a single population, they must convey the richness, complexity, and precision of auditory information as they shape signals transmitted to the brain. To understand better the sophistication of spiral ganglion response properties, we compared somatic whole-cell current-clamp recordings from basal and apical neurons obtained during the first 2 postnatal weeks from CBA/CaJ mice. We found that during this developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 63 publications
4
33
1
Order By: Relevance
“…Activation of K v channels shapes the pattern of neuronal firing and excitability and drives the rate of adaptation to sustained stimuli 23 . Their differential expression could participate in the expected distinct physiological characteristics of the different subclasses of type I neurons 5 , 8 , 24 (Fig. 3d–f and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of K v channels shapes the pattern of neuronal firing and excitability and drives the rate of adaptation to sustained stimuli 23 . Their differential expression could participate in the expected distinct physiological characteristics of the different subclasses of type I neurons 5 , 8 , 24 (Fig. 3d–f and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, altered neuronal membrane potential abolished rebound burst firing in thalamocortical neurons (Kim and McCormick, 1998). In spiral ganglion neurons, the regulation of holding potential on neuronal output was also observed in a subset of rapidly accommodating neurons that could be transformed into slowly accommodating neurons with a change of holding potential (from -80 to -60 mV, Crozier and Davis, 2013). …”
Section: Discussionmentioning
confidence: 95%
“…The endogenous properties of spiral ganglion neurons in explant cultures undergo dramatic changes in intrinsic excitability during the first 2 weeks prior to hearing onset (Crozier and Davis, 2013). The majority of changes in excitability stabilize by postnatal day 4 (P4) such that spiral ganglion neurons from P14 animals retain both regional as well as tonotopic characteristics of voltage thresholds presented herein (Crozier and Davis, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that exogenous NTs enhanced survival and neurite extension in vitro . Kondo et al demonstrated that SGN survival and neurite number were more strongly enhanced by NT3 than by BDNF at E18 culture, and Jin et al showed that combinations of NTs (NT3 + BDNF + leukemia inhibitory factor) could increase SGN survival better than single or other combinations, and these NTs were known to modulate neuronal activity through ion channel regulations …”
Section: Discussionmentioning
confidence: 99%